Expression profiling of human hepatoma cells reveals global repression of genes involved in cell proliferation, growth, and apoptosis upon infection with parvovirus H-1 - Li, Jianhong; Rommelaere, Jean (Journal of virology, 2005)
Autonomous parvoviruses are characterized by their stringent dependency on host cell S phase and their cytopathic effects on neoplastic cells. To better understand the interactions between the virus and its host cell, we used oligonucleotide arrays that carry more than 19,000 unique human gene sequences to profile the gene expression of the human hepatocellular carcinoma cell line QGY-7703 at two time points after parvovirus H-1 infection. At the 6-h time point, a single gene was differentially expressed with a >2.5-fold change. At 12 h, 105 distinct genes were differentially expressed in virus-infected cells compared to mock-treated cells, with 93% of these genes being down-regulated. These repressed genes clustered mainly into classes involved in transcriptional regulation, signal transduction, immune and stress response, and apoptosis, as exemplified by genes encoding the transcription factors Myc, Jun, Fos, Ids, and CEBPs. Quantitative real-time reverse transcription-PCR analysis on selected genes validated the array data and allowed the changes in cellular gene expression to be correlated with the accumulation of viral transcripts and NS1 protein. Western blot analysis of several cellular proteins supported the array results and substantiated the evidence given by these and other data to suggest that the H-1 virus kills QGY-7703 cells by a nonapoptotic process. The promoter regions of most of the differentially expressed genes analyzed fail to harbor any motif for sequence-specific binding of NS1, suggesting that direct binding of NS1 to cellular promoters may not participate in the modulation of cellular gene expression in H-1 virus-infected cells.
Gesehen am 19.02.2021